2020
DOI: 10.1109/jphot.2020.2993603
|View full text |Cite
|
Sign up to set email alerts
|

Air-Mode Photonic Crystal Micro-Ring Resonator With Enhanced Quality Factor for Refractive Index Sensing

Abstract: Intense light-matter interaction is critical for enabling high-sensitivity refractive index sensors, high-efficiency light sources, and high-performance nonlinear devices. A bowtie-hole photonic crystal micro-ring resonator is proposed and numerically demonstrated to enhance the light-matter interaction effectively through achieving strong spatial and temporal light confinement, simultaneously. Through engineering the photonic crystal unit cell, the bowtie-hole photonic crystal is proved to possess the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The amount of splitting remained almost constant upon changing the temperature of the chip and the RI of the top cladding, cancelling their effect on the sensor signal. Xu et al [23] have shown a bowtie-hole photonic crystal-based MRR to enhance light-matter interaction and have reported 200 nm RIU −1 sensitivity. A metalassisted Si strip waveguide has been designed in which the inserted thin metal layer under cladding elevates the energy in upper cladding region, providing a maximum RI sensitivity of 300 nm RIU −1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of splitting remained almost constant upon changing the temperature of the chip and the RI of the top cladding, cancelling their effect on the sensor signal. Xu et al [23] have shown a bowtie-hole photonic crystal-based MRR to enhance light-matter interaction and have reported 200 nm RIU −1 sensitivity. A metalassisted Si strip waveguide has been designed in which the inserted thin metal layer under cladding elevates the energy in upper cladding region, providing a maximum RI sensitivity of 300 nm RIU −1 [24].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this dilemma, many researchers have proposed different optimization schemes for strip waveguide microrings. Ultra-thin waveguide microrings [7], Bragg grating microrings [19,20], slot waveguide microrings [21][22][23], and photonic crystal waveguide microrings [24,25] are utilized to achieve refractive index sensors with sensitivities of 133 nm/RIU [7], 297 nm/RIU [19], 298 nm/RIU [23], and 200 nm/RIU [24], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various structures of MRR sensors have been developed to improve their sensitivity. For example, a one-dimensional photonic crystal MRR with periodic air holes is introduced in a microring waveguide [20][21][22], grating-type MRR [23][24][25], and SMRR [26][27][28][29][30][31][32]. The SMRR introduces an air slot in microring waveguides, where the evanescent field of each individual silicon brick is extremely high, constructively guiding the quasi-TE mode into the slot region to interact with the matter [26].…”
Section: Introductionmentioning
confidence: 99%